2017
DOI: 10.1111/eva.12564
|View full text |Cite
|
Sign up to set email alerts
|

Next‐generation metrics for monitoring genetic erosion within populations of conservation concern

Abstract: Genetic erosion is a major threat to biodiversity because it can reduce fitness and ultimately contribute to the extinction of populations. Here, we explore the use of quantitative metrics to detect and monitor genetic erosion. Monitoring systems should not only characterize the mechanisms and drivers of genetic erosion (inbreeding, genetic drift, demographic instability, population fragmentation, introgressive hybridization, selection) but also its consequences (inbreeding and outbreeding depression, emergenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
116
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 181 publications
3
116
1
4
Order By: Relevance
“…Bold text indicates nonoverlapping HPDI values km Assessing genetic erosion in this species is important for identifying areas of management focus, particularly where the monitoring of demographic parameters may be costly and difficult (Leroy et al, 2018). Rows represent the populations from which each individual was sampled, and columns represent the population from which they migrated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bold text indicates nonoverlapping HPDI values km Assessing genetic erosion in this species is important for identifying areas of management focus, particularly where the monitoring of demographic parameters may be costly and difficult (Leroy et al, 2018). Rows represent the populations from which each individual was sampled, and columns represent the population from which they migrated.…”
Section: Discussionmentioning
confidence: 99%
“…Although a variety of metrics have been proposed for assessing genetic erosion (Hoban et al, 2014;Leroy et al, 2018) (Galpern, Manseau, & Wilson, 2012;Schaefer, 2003). Although a variety of metrics have been proposed for assessing genetic erosion (Hoban et al, 2014;Leroy et al, 2018) (Galpern, Manseau, & Wilson, 2012;Schaefer, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…() surveyed 162 SNPs in golden eagles and found that mean observed heterozygosity (H O ) was 0.32 ± 0.01 in juveniles whereas adult H O was 0.35 ± 0.01, a significant statistical difference consistent with expectations of viability selection. Unfortunately, the types of SNP arrays often used in MIS studies preclude the evaluation of other genetic diversity metrics that will likely be important in the future (e.g., runs‐of‐homozygosity or copy number variants, see Leroy et al., ). This is a factor worth considering when planning a study, as evaluating change in genetic diversity metrics over time is an important task of genetic monitoring (see Box 3).…”
Section: Questions and Metrics That Can Be Investigated With Mismentioning
confidence: 99%
“…This highlights the fact that the transition from conservation genetics to conservation genomics will not be limited by the availability of data, but what we do with it. Recent reviews argue that new statistical methods are required to convert this wealth of genomic data into practical management outcomes for endangered populations and species (Leroy et al, 2017). By inferring the impact of a barrier on patterns of relatedness and dispersal using genomic data and the AC, F I G U R E 1 Pyrenean desman (Galemys pyrenaicus; centre right) and the barriers to its dispersal found using kinship and network analyses in Escoda et al (2018).…”
mentioning
confidence: 99%